LOCATIVE SYNTACTIC-SEMANTIC CONSTRUCTIONS WITH PREPOSITION “ON” - Jumanazarov Samandar Urinovich (European Science Publishing, 2024)
The syntaxes considered in this section differ from all previous syntaxes in their syntax and semantic features. They constitute the paradigmatic series of interactive syntaxes that are categorized as substantial. Consider the following sentences, in which prepositional combinations are endowed with syntactic semantic sign of interactivity (repeatability, repetition, multiple) The article presents theoretical ideas in this regard and proves them with examples.
Keywords: Location; orientation; combination; dependent; demonstrated; replacement; public; union’ tribe; repeatability; repetition; multiple; connotative.